Increased Platelet-CD4+ T Cell Aggregates Are Correlated With HIV-1 Permissiveness and CD4+ T Cell Loss - Dai, Xiao-Peng; Wu, Feng-Ying; Cui, Cheng; Liao, Xue-Jiao; Jiao, Yan-Mei; Zhang, Chao; Song, Jin-Wen; Fan, Xing; Zhang, Ji-Yuan; He, Qing; Wang, Fu-Sheng (Frontiers in Immunology, 2021)
Chronic HIV-1 infection is associated with persistent inflammation, which contributes to disease progression. Platelet-T cell aggregates play a critical role in maintaining inflammation. However, the phenotypic characteristics and clinical significance of platelet-CD4+ T cell aggregates remain unclear in different HIV-infected populations. In this study, we quantified and characterized platelet-CD4+ T cell aggregates in the peripheral blood of treatment-naïve HIV-1-infected individuals (TNs), immunological responders to antiretroviral therapy (IRs), immunological non-responders to antiretroviral therapy (INRs), and healthy controls (HCs). Flow cytometry analysis and immunofluorescence microscopy showed increased platelet-CD4+ T cell aggregate formation in TNs compared to HCs during HIV-1 infection. However, the frequencies of platelet-CD4+ T cell aggregates decreased in IRs compared to TNs, but not in INRs, which have shown severe immunological dysfunction. Platelet-CD4+ T cell aggregate frequencies were positively correlated with HIV-1 viral load but negatively correlated with CD4+ T cell counts and CD4/CD8 ratios. Furthermore, we observed a higher expression of CD45RO, HIV co-receptors, HIV activation/exhaustion markers in platelet-CD4+ T cell aggregates, which was associated with HIV-1 permissiveness. High levels of caspase-1 and caspase-3, and low levels of Bcl-2 in platelet-CD4+ T cell aggregates imply the potential role in CD4+ T cell loss during HIV-1 infection. Furthermore, platelet-CD4+ T cell aggregates contained more HIV-1 gag viral protein and HIV-1 DNA than their platelet-free CD4+ T cell counterparts. The platelet-CD4+ T cell aggregate levels were positively correlated with plasma sCD163 and sCD14 levels. Our findings demonstrate that platelet-CD4+ T cell aggregate formation has typical characteristics of HIV-1 permissiveness and is related to immune activation during HIV-1 infection.